Both bulk and cancer stem cell subpopulations in triple‐negative breast cancer are susceptible to Wnt, HDAC, and ERα coinhibition. Issue 24 (9th December 2016) - Sulaiman, Andrew; Sulaiman, Brandon; Khouri, Lara; McGarry, Sarah; Nessim, Carolyn; Arnaout, Angel; Li, Xuguang; Addison, Christina; Dimitroulakos, Jim; Wang, Lisheng
Abstract : Development of targeted therapies for triple‐negative breast cancer (TNBC, a more aggressive subtype) is an unmet medical need. We analyzed data from 887 patients with invasive breast cancer and observed that increased Wnt and histone deacetylase (HDAC) activities are associated with estrogen receptor 1 (ESR1) and progesterone receptor (PGR) repression, poor survival, and increased relapse. The inverse correlation between Wnt signaling and repression of ESR1 and PGR expression was found to be magnified in cancer stem cell (CSC) subpopulations in TNBC cell lines. Cosuppression of Wnt, HDAC, and ESR1 using clinically relevant low‐dose inhibitors effectively repressed both bulk and CSC subpopulations and converted CSCs to non‐CSCs in TNBC cells without affecting MCF‐10A mammary epithelial cells. Abstract :